A novel KIR3DL1*0200102 allele isolated from a West African donor by sequence-based typing - Yindom, L; De Silva, T; Rowland-Jones, S (Blackwell Publishing Ltd, 2014)
KIR3DL1*0200102 allele differs from KIR3DL1*0200101 with four single nucleotide polymorphisms in introns 5 and 6, respectively. © 2014 John Wiley and Sons A/S. Published by John Wiley and Sons Ltd.